Scholastic atlas of Earth. - Scholastic Reference (Firm) (New York : Scholastic Reference, 2004)
Presents an overview of the physical geography of the earth, fromits molten core to its highest mounatin peak, providing illustrated information on rocks, soil, erosion, water, climate, ecosystems, and more.
Includes index.
Horn Book.
8.8
3-6
Keywords: Earth -- Juvenile literature; Earth; Earth